2022
DOI: 10.3889/oamjms.2022.8962
|View full text |Cite
|
Sign up to set email alerts
|

South Sulawesi Milkfish (Chanos Chanos) Scale Waste as a New Anti-inflammatory Material in Socket Preservation

Abstract: BACKGROUND: One of South Sulawesi’s huge brackish water fishery product is milkfish (Chanos chanos). Scales are wasted in milkfish processing. However, they are a good source of chitosan, which has been found to promote anti-inflammation, wound healing, and bone regeneration. AIM: This study aims to determine the effect of milkfish scales waste on the inflammatory response of wound healing after tooth extraction by tumor necrosis factor-alpha (TNF-α) and interleukin (IL)-6 analysis. METHODS: This is a post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that the optimum approach for utilizing fish scales is either directly as food or indirectly to produce supplements for feed. In a study by, 47 milkfish can contain up to 37.4% chitosan following dehydration. Furthermore, antibacterial chemicals identified in scales of fish exhibiting bone‐like compositions may be used as dental restorations.…”
Section: Sources Of Chitin and Chitosanmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that the optimum approach for utilizing fish scales is either directly as food or indirectly to produce supplements for feed. In a study by, 47 milkfish can contain up to 37.4% chitosan following dehydration. Furthermore, antibacterial chemicals identified in scales of fish exhibiting bone‐like compositions may be used as dental restorations.…”
Section: Sources Of Chitin and Chitosanmentioning
confidence: 99%
“…46 Chitin, calcium, a mineral proximate, alkaloid compounds, steroids, saponins, phenol hydroquinone, molisch, benedict, biuret, and ninhydrin are compounds found in scales of fish. 47 The scalar structure has been determined to be separated into two parts: a thin outer covering comprised of highly mineralized hyalodentin and a thick interior basal plate. 48 Pigments, hydroxyapatite crystals, and fibrous collagen arranged haphazardly, make up the composition of the hyalodentin layer.…”
Section: From Fish Scalementioning
confidence: 99%
See 1 more Smart Citation
“…The results of this production activity are hard organic waste in the form of fish scales, skin and bones, which have the potential to pollute the environment, so it is necessary to process these wastes into products with selling value, including as a raw material for collagen 5 . Utilization of fish scale waste can be used as raw materials for chips, crackers, chitosan, collagen, and others 6,7 .…”
Section: Introductionmentioning
confidence: 99%